Emerging tools, enabling technologies, and future opportunities for the bioproduction of aromatic chemicals. Issue 1 (10th August 2018) - Machas, Michael; Kurgan, Gavin; Jha, Amit K; Flores, Andrew; Schneider, Aidan; Coyle, Sean; Varman, Arul M; Wang, Xuan; Nielsen, David R
Abstract: Aromatic compounds, which are traditionally derived from petroleum feedstocks, represent a diverse class of molecules with a wide range of industrial and commercial applications. Significant progress has been made to alternatively and sustainably produce many aromatics from renewable substrates using microbial biocatalysts. While the construction of both natural and non‐natural pathways has expanded the number and diversity of aromatic bioproducts, pathway modularization in both single‐ and multi‐strain systems continues to support the enhancement of key production metrics towards economically‐viable levels. Emerging tools for implementing more precise metabolic control (e.g. CRISPRi, sRNA) as well as the engineering of novel high‐throughput screening platforms utilizing in vivo aromatic biosensors, meanwhile, continue to facilitate further optimization of both pathways and hosts. While product toxicity persists as a key challenge limiting the production of many aromatics, various successful strategies have been demonstrated towards improving tolerance, including via membrane and efflux pump engineering as well as by exploiting alternative production hosts. Finally, as a further step towards sustainable and economical aromatic bioproduction, non‐model substrates including lignin‐derived compounds continue to emerge as viable feedstocks. This review highlights recent and notable achievements related to such efforts while offering future outlooks towards engineering microbial cell factories for aromatic production. © 2018 Society of Chemical Industry